Sheep farmer opinions on the current and future role of veterinarians in flock health management on sheep farms: a qualitative study - Kaler, Jasmeet; Green, L.E. (Elsevier, 2013)
A 2009 UK Government report on veterinary expertise in food animal production highlighted that there was insufficient herd health expertise among veterinarians and lack of appropriate business models to deliver veterinary services to the livestock sector. Approximately two thirds of sheep farmers only contact their veterinarian for emergencies and one fifth have all year round contact. The aim of the current study was to understand sheep farmers’ perception, the current and future role of veterinarians in flock health management using qualitative methodology. The eligibility criteria were male farmers with a flock size of at least 200 adult sheep. Seven focus groups of farmers (n = 45) stratified by three regions and two age groups (≤50 and >50) were conducted. Thematic analysis of the discussions indicated that most farmers considered and used their veterinarian as a fire-fighter, whilst other advice was gathered free of charge when the veterinarian was on the farm for other reasons (typically seeing cattle) or by telephone. A small group of farmers were using their veterinarian or a sheep consultant proactively with regular contact and found this financially beneficial. Farmers indicated that the key barriers to using a veterinarian proactively were inconsistent service, high turnover of veterinarians, lack of expertise of sheep farming among veterinarians and concern about independence of advice. Although economics was also mentioned as a key barrier to using veterinarians more proactively, most farmers did not know where they gained and lost income from their flock; there was heavy reliance on the single farm payment scheme (SPS) and very few farmers kept records from which they could investigate where there were inefficiencies in production. Overall sheep farmers considered sheep farming complex and that each farm was unique and that they themselves were the experts to manage their flock. We conclude that there is an impasse: veterinarians might need to provide consistency and wide expertise beyond knowledge of disease and a model of how flock planning would be financially beneficial but until sheep farmers keep production records flock health planning cannot be rigorous and the financial benefits cannot be evaluated. Given the reliance on SPS by farmers an alternative model would be to require farmers to keep production records to comply with SPS. This might lead to flock health planning being adopted at a faster rate and so develop the UK sheep industry and make it more environmentally sustainable by reducing waste from disease and low productivity.